2022
DOI: 10.1111/jonm.13656
|View full text |Cite
|
Sign up to set email alerts
|

From anticipation to confidence: A descriptive qualitative study of new graduate nurse communication with physicians

Abstract: Aim The aim of this study was to understand how new graduate nurses experience communication with physicians. Background Communication is necessary for high‐quality health care delivery. With poor patient outcomes as a driving force, knowledge of the dialogue that occurs between new graduate nurses and physicians has been rarely explored. Methods This qualitative descriptive study involved 13 new graduate nurses from an academic teaching hospital in the south‐eastern United States. Data for this study were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nurses are required to be well-equipped to handle communication challenges (Scibilia et al, 2022). Forbes III and Evans (2022) found that new graduate nurses felt unprepared for their nursing education programs to communicate with physicians and experienced discomfort and anxiety with communication. In a study of over 3000 nurse leaders, Berkow et al (2009) found that less than 50% of nurse leaders assessed their new graduate nurses as satisfactory in communication with physicians, as a member of an interprofessional team, and in patient advocacy and patient education.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are required to be well-equipped to handle communication challenges (Scibilia et al, 2022). Forbes III and Evans (2022) found that new graduate nurses felt unprepared for their nursing education programs to communicate with physicians and experienced discomfort and anxiety with communication. In a study of over 3000 nurse leaders, Berkow et al (2009) found that less than 50% of nurse leaders assessed their new graduate nurses as satisfactory in communication with physicians, as a member of an interprofessional team, and in patient advocacy and patient education.…”
Section: Introductionmentioning
confidence: 99%